Physicochemical monitoring of wastewater from a sugar and ethanol industry after bioaugmentation, with a proposal for reuse - Perovano Filho, Natalino; Silva, Kelly Fernanda Seára da; Santos, Elane Cristina Lourenço dos; Queissada, Daniel Delgado; López, Ana Maria Queijeiro (Acta Scientiarum. Technology, 2016)
The sugar and ethanol industry generates large quantities of waste liquids. If untreated effluents are used in fertigation, they might contaminate groundwater and, if they are released into water bodies, they might also jeopardize the survival of the aquatic ecosystem. Therefore, the proposal of this study was to isolate microorganisms from the treatment station of a sugar and ethanol industry, assessing their enzymatic behavior and effects in laboratory, as well as the physicochemical improvement of the effluent. Following a bioaugmentation of the effluent, a physicochemical monitoring was performed with the purpose of reusing it in drip irrigation. Â 